Réflexions linguistiques et sémiologiques pour une écriture didactique du multimédia de langues - Anne-Laure Foucher (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Assuming CALL to need language didactics, assuming didactics to need linguistics and CALL to need minimal " semiologic " reflections, we show how is profitable to adopt a didactic point of view linking linguistic and semiologic aspects in order to examine the contributions to learning of a multimedia approach for foreign languages. To complete these theorical considerations, we propose to set out methodological advice to design a multimedia approach for language learning and teaching.